Scaling Law for Hysteresis Losses in Round Superconductors Magnetized by Alternating, Rotating or Elliptical Magnetic Fields - Lorin, Clement; Netter, Denis; Masson, Philippe J. (IEEE transactions on applied superconductivity, 2015)
AC losses in an isolated superconducting round wire with a power-law electrical behavior produced by the combined effect of transverse alternating and rotating fields, i.e., an elliptical field, are investigated. The goal is to provide semianalytical expressions of the magnetization losses with a high enough reliability to be used in sizing code development or optimization methods. The fit expressions are based on data generated by means of a 2-D numerical model using the well-known and proved H-formulation. In the meantime, data processing allows for revealing a universal variable cn of utmost importance in magnetization loss calculation. This variable depends on the n-value of the power-law resistivity, and both the dimensionless magnetic field b* and frequency f*.